NATURAL-RESOURCE POTENTIAL OF AGRO-ECOSYSTEMS: AN ANALYSIS OF THE CONCEPTUAL AND CATEGORICAL APPARATUS, JUSTIFYING CONTEMPORARY INTERPRETATIONS - Рідей, Н. М.; Горбатенко, А. А.; Кучеренко, Ю. А.; Пашутіна, О. М. (Scientific Progress & Innovations, 2013)
The concept of different potentials in agro-ecosystems was analyzed. The natural resources potential of agricultural land was reasonably determined. The authors propose a landscape-indicator approach to the assessment of agricultural landscapes by establishing an index of their natural resource potential of the main factors of anthropogenic influence in the agricultural sphere.